Senam Hamil Berpengaruh Terhadap Tingkat Kecemasan pada Primigravida Trimester III di RSIA Sakina Idaman Sleman, D. I Yogyakarta - Farida Aryani; Akbar Raden; Ismarwati Ismarwati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
The anxieties that suffered by pregnant mother are about pregnancy, labor and the role as the mother. Pregnant women will also be transmitting physical effects to the fetus out his emotions, if concerns increase will affect fetus. Increased chemically and hormone levels generated by these qualm will circulate in the body and penetrate the placenta until the fetus. In the form of a trimester III anxiety pregnant women namely maternity doubt can normally, fear is not able to withstand pain during childbirth, the health of babies after birth, smoothness childbirth, the state of pregnant women after childbirth, childbirth is not appropriate desire, not directly meet baby after childbirth, and that diminished attention from others. Information about the experience of deliveries scary also increased anxiety on pregnant women. Factors that affects anxiety for pregnant women of them are lack of support family, sufficiency financial, stress of the neighborhood, the ability mastery pregnancy, and information about experiences deliveries scary. Complication in pregnancy resulting from burden psychological can be reduced or is eliminated by provide treatment and activity sports during pregnancy. This study to knows the influence of pregnancy exercise in reducing the anxiety on primigravida third trimester. Design of Research is quasi experiment with pretest–post test non equivalent control group design. The amount of sample of research was 56 people with accidental sampling. Analysis of univariabel showed each of variable. Analysis of bivariabel used t-test and regresi of linier to analysis of multivariabel. The approximately of the anxiety for the first group (the group that given the pregnancy exercise) is lower -4.3±3.8 than another group/second group (that group that didn’t given the pregnancy exercise) 0.8±1.2. The result t-test p 0.00001<0.05. Variable of outside that influent toward the anxiety are education and income with value p>0.05.